Intellectual Agility Stimulation to Improve Organizational Performance - Sutrisno Sutrisno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to develop theoretical leadership and organization, which describes the dimensions of Intellectual Capital, Intellectual Property and Organizational Performance. Based on the substantive and strategic dimensions of generating new concepts, the theory of intellectual agility stimulation (intellectual property) becomes a stimulus for the leader’s thinking in making decisions in the right time, condition and situation. This study employs in depth literature review from main source. Based on a complete and in-depth literature review, the empirical model of research shows that sharing knowledge that includes donating, collecting will trigger an increase in Intellectual Agility Stimulus and Professional competence. As a result, it will improve the performance of organizations that are ready to face the industrial revolution 4.0.